2013
DOI: 10.1056/nejmoa1303989
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib versus Sunitinib in Metastatic Renal-Cell Carcinoma

Abstract: Pazopanib and sunitinib have similar efficacy, but the safety and quality-of-life profiles favor pazopanib. (Funded by GlaxoSmithKline Pharmaceuticals; COMPARZ ClinicalTrials.gov number, NCT00720941.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

77
1,263
17
74

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 1,708 publications
(1,431 citation statements)
references
References 20 publications
77
1,263
17
74
Order By: Relevance
“…The aim was to induce stability of disease prior to nephrectomy in over 75% of patients, avoiding potential progression and clinical deterioration during the preoperative surgical period. The PFS and OS results [7.1 months and 22.7 months respectively] were acceptable and in line with those seen for similar risk groups in the pivotal randomized VEGF targeted therapy trials in which the majority of patients previously had nephrectomy [10][11][12] . Survival analysis showed that the prognostic factors in this specific group of patients are similar to those in unselected patients.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The aim was to induce stability of disease prior to nephrectomy in over 75% of patients, avoiding potential progression and clinical deterioration during the preoperative surgical period. The PFS and OS results [7.1 months and 22.7 months respectively] were acceptable and in line with those seen for similar risk groups in the pivotal randomized VEGF targeted therapy trials in which the majority of patients previously had nephrectomy [10][11][12] . Survival analysis showed that the prognostic factors in this specific group of patients are similar to those in unselected patients.…”
Section: Discussionsupporting
confidence: 74%
“…Both drugs have clinical benefit rates above 70% in this setting although the sunitinib trials focused mainly on safety rather than efficacy. Previous non-inferiority studies show these agents are non-inferior in terms of efficacy with differing adverse event profiles 11 . Our results support these findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HRQoL was assessed with the functional assessment of chronic illness therapy-fatigue (FACIT-F) questionnaire, the National Comprehensive Cancer Network/functional assessment of cancer therapy-kidney symptom index 19 (NCCN-FACT FKSI-19), and the cancer therapy satisfaction questionnaire. The study was open label50 …”
Section: Resultsmentioning
confidence: 99%